1982
DOI: 10.1051/jphys:019820043080122700
|View full text |Cite
|
Sign up to set email alerts
|

The crystal structure of KCdF3

Abstract: The crystal structure of KCdF3 is determined in the third, orthorhombic phase and refined by using a full matrix least-squares method by taking domain structures into consideration. Refinement is performed with superlattice-X, M and R point reflection intensity data collected on the multiple-film Weissenberg photographs taken with filtered MoKα radiation. Pbnm-D16 2h (z = 4) is assigned to the space group of KCdF3. The R value reaches 8 % for the intensity data of the X and M point reflections. When the R poin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1983
1983
2013
2013

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Some kinds of superlattice reflections are observed at room temperature by the structural transitions. The structure in phase I11 was determined to be of orthorhombic symmetry D;:-Pbnm regarding the population ratio of poly-domains in the used single crystal [4]. By indexing the reflections, the superlattice reflections were confirmed to be a t the GI CH SH AS SP TB GH TE MI, R-, and X-points in the reciprocal space.…”
Section: Big 4; Experimental Arrangement In the Edd Methodsmentioning
confidence: 99%
“…Some kinds of superlattice reflections are observed at room temperature by the structural transitions. The structure in phase I11 was determined to be of orthorhombic symmetry D;:-Pbnm regarding the population ratio of poly-domains in the used single crystal [4]. By indexing the reflections, the superlattice reflections were confirmed to be a t the GI CH SH AS SP TB GH TE MI, R-, and X-points in the reciprocal space.…”
Section: Big 4; Experimental Arrangement In the Edd Methodsmentioning
confidence: 99%
“…Na6Al3F14 (150,152) chiolites Framework Structures type example AMF3: perovskites NaNiF3, NaCuF3 (154)(155)(156), K4Mn3F12 (164) AxMF3: bronzes KMF3, KCuF3 (157)(158)(159)(160)(161)(162)(163), Cs2Ba2Cu3F12 (127,164) K06FeF3 TTB (165,166) AIMIIMlnF6: pyrochlores CSo 2Zn02Fe0 gF3 HTB (167,168) FeF3-0.33H2O HTB (169) RbNiCrF6 (67,170,171) AI2MuMmF7: weberites CsAgFeF6, NH4Fe2F6 (172-174)…”
Section: Aumf4mentioning
confidence: 99%
“…We found that for the band structure calculations, 101 k-points were enough to obtain good results. For the optical calculations, however, the irreducible Brillouin zone was sampled with 1000 k-points for NaCdF 3 .…”
Section: Calculation Methodsmentioning
confidence: 99%
“…However, several alkaline earth cadmium trifluoride compounds, MCdF 3 (M = K, Rb, Cs), have been synthesized experimentally which have not exhibited ferroelectricity [3,4]. In the predicted ferroelectric phase, NaCdF 3 has a rhombohedral structure with two NaCdF 3 molecules (ten atoms) per unit cell.…”
mentioning
confidence: 98%